2000
DOI: 10.1128/jb.182.6.1624-1631.2000
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Mutational Analysis of the Uptake Hydrogenase of the Filamentous Cyanobacterium Anabaena variabilis ATCC 29413

Abstract: A 10-kb DNA region of the cyanobacterium Anabaena variabilis ATCC 29413 containing the structural genes of the uptake hydrogenase (hupSL) was cloned and sequenced. In contrast to the hupL gene of Anabaena sp. strain PCC 7120, which is interrupted by a 10.5-kb DNA fragment in vegetative cells, there is no programmed rearrangement within the hupL gene during the heterocyst differentiation of A. variabilis. The hupSL genes were transcribed as a 2.7-kb operon and were induced only under nitrogen-fixing conditions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
120
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(131 citation statements)
references
References 54 publications
8
120
0
3
Order By: Relevance
“…strain PCC 7120 demonstrated that hupL transcription coincides with the formation of heterocysts. Subsequent studies, in other filamentous strains, have confirmed the induction of an hupL transcript under nitrogen-fixing conditions only (Axelsson et al, 1999;Happe et al, 2000; Hansel et al, 2001). One exception is Anabaena variabilis ATCC 29413, where a low level of hupL expression has been detected in vegetative cells grown with the addition of ammonia (Boison et al, 2000).…”
mentioning
confidence: 97%
“…strain PCC 7120 demonstrated that hupL transcription coincides with the formation of heterocysts. Subsequent studies, in other filamentous strains, have confirmed the induction of an hupL transcript under nitrogen-fixing conditions only (Axelsson et al, 1999;Happe et al, 2000; Hansel et al, 2001). One exception is Anabaena variabilis ATCC 29413, where a low level of hupL expression has been detected in vegetative cells grown with the addition of ammonia (Boison et al, 2000).…”
mentioning
confidence: 97%
“…100 µmol H 2 /mg chlorophyll a/h, with light conversion efficiencies of up to 3.9 % (proportion of absorbed light energy converted to H 2 ) (Dutta et al 2005;Yoon et al 2006;. Rates were increased 3-7 fold in Anabaena mutants deficient in uptake hydrogenase activity (Borodin et al 2000;Happe et al 2000;Masukawa et al 2002;Yoshino et al 2007) and this strategy was applied in outdoor culture. However, the maximum light conversion efficiency was only 0.1 %, which has implications for the large scale application of this approach (Lindblad et al 2002;Tsygankov et al 2002).…”
Section: 11: Photoautotrophic Microorganismsmentioning
confidence: 99%
“…Elimination of Hup activity resulted in a 4-to 7-fold increase in the rates of H 2 production in an Ar atmosphere compared with wild-type cells, while the effects of inactivation of Hox activity on H 2 production were not evident under the conditions tested. Hup-disrupted mutants also were shown to be effective in enhancing H 2 production by several other Anabaena and Nostoc strains of cyanobacteria (Happe et al 2000;Lindberg et al 2002;Schütz et al 2004;Carrasco et al 2005;Yoshino et al 2007). A promising approach to further improve photobiological H 2 production in the presence of O 2 is to initially select parental strains with high nitrogenase activity and inactivate their Hup activities.…”
Section: Inactivation Of Uptake Hydrogenase (Hup)mentioning
confidence: 99%